Pengembangan Kurikulum Berbasis Proyek untuk Meningkatkan Kreativitas dan Kolaborasi Siswa - Hasbullah, Hasbullah; Mahmudah, Mahmudah (STKIP PGRI SITUBONDO, 2024)
The development of this curriculum is designed with an approach that integrates project-based learning that is made in various subjects. This study aims to develop and evaluate a project-based curriculum to improve students' creativity and collaboration. This research method uses literature study (library research). The findings found that the development of this project-based curriculum was carried out so that students could explore, design, and implement learning concepts in real contexts. This process not only hones critical thinking skills but also interpersonal communication skills. The purpose of this study is to evaluate the effectiveness of the project-based curriculum in improving students' creativity and collaboration.